The RCEP in an emerging multipolar order: examining energy transition implications - Chatzinikolaou, Dimos; Vlados, Charis Michael (Frontiers in Political Science, 2025)
This paper examines how the Regional Comprehensive Economic Partnership (RCEP) influences global energy transition within an emerging multipolar world order. Using the New Globalization Scenario Matrix (NGSM) framework and correlative SWOT analysis, the study identifies a “medium-high performance” scenario as most probable, characterized by gradual regional integration constrained by geopolitical tensions and governance gaps. The analysis reveals asymmetric energy transition contributions: strong support for renewable energy deployment through trade and investment channels, but limited coordination for decarbonization policies due to absent binding environmental commitments. The study proposes complementary institutional frameworks to enhance the RCEP’s energy transition contributions while addressing identified governance deficits in environmental coordination.